Talk it, win it: exploring the link between coaches’ communication skills and athlete satisfaction in KARISMA sport teams athletes - Mohd Aznan, Ellail Ain; Abdul Hamid, Ayu Izzati; Abu Bakar, Al Hafiz; Mohd Yazid, Siti Amalina; Kamaruddin, Harris Kamal; Md Yusof, Mohd Khairulanwar (Universiti Teknologi MARA, Perlis, 2025)
Athletes who perceive their coaches as effective communicators tend to exhibit higher levels of motivation, engagement and satisfaction, especially during their training routines. The enhancement and engagement are also often attributed to the coach’s ability to clearly convey messages, expectations and constructive feedback. In this study, a total of 100 questionnaires were distributed to the athletes of Sukan Mahasiswa (KARISMA) from Universiti Teknologi MARA (UiTM) Perlis Branch in examining the influence of perceived communication skills on athletes’ satisfaction. The instruments employed included a modified version of the Interpersonal Communication Skills Inventory (ICSI; 10 items), and the Satisfaction Scale for Athlete (SSA; 14 items). Pearson Correlation was used in analyzing the relationship between communication skills and athletes’ satisfaction. Result revealed a moderate positive correlation between perceived communication skills and athletes’ satisfaction (r=.619**, p<0.05). The finding underscores the importance of effective communication skills in enhancing athlete satisfaction and highlights the need for coaches to develop strong interpersonal communication competencies.